Effects of Motherhood and Selection into Motherhood: Revisiting the 2007 Parental Benefits Reform in Germany - Arnim Seidlitz; Bernd Fitzenberger (ZBW - Leibniz Information Centre for Economics, 2021)
This paper studies the causal effect of giving first birth and how that effect changes by the 2007 reform in parental benefits in Germany. We further investigate how the reform affects the selection of women into motherhood and how that selection effect affects labor market outcomes. A large novel data set merging data from the pension insurance with administrative labor market data provides information on all births. We apply a dynamic treatment effect approach which differs from other strategies used so far in most of the literature to estimate the causal effect of motherhood and to evaluate the 2007 reform. The reform has positive medium-run effects on earnings and employment while reducing full-time employment. There are no effects on second-order fertility. While the reform slightly changes the selection of mothers, this has little impact on the reform effect for the causal effect of motherhood.
Keywords: J08; J13; J16; J22; 330; Parental leave reform; causal effect of motherhood; earnings; employmentdynamic treatment effect